Space, place, and power in South African writing centres: Special issue in honour of Sharifa Daniels - Richards, Rose; Lackay, Anne-Mari; Delport, Selene (Stellenbosch Papers in Linguistics Plus, 2019)
A writing center cannot define itself as a space—we’re often kicked out of our spaces. It’s not a pedagogy. We’re always re-articulating our pedagogy. It’s certainly not an academic department. It crosses all disciplines. A writing center does not produce a text—the texts in writing centers are unfinished. And we don’t own the texts our students create; those texts are cross-curricular, cross-linguistic, cross-discursive.(Sunstein 1998: 8–9)